Exploring the implementation of the TIME Home Learning programme and learning trajectories of 5- to 7-year-olds: Introduction to the TIME study - von Blottnitz, Magali (My University, 2024)
This is the first in a series of learning briefs that explore the implementation of the TIME Home Learning programme and the learning trajectories of 5- to 7-year-olds. This brief focuses on key elements of the programme, and also on the design of a study to explore how it is embedded in the ecosystem and lived in practice.
More information about the TIME (Together in My Education) home-learning programme and materials can be found in open access at: https://wwhomeliteracy.org.za/time/
Keywords: Early learning; Early literacy; South Africa; Wordworks; Home-learning; Parental involvement; Longitudinal study; Grade R; Grade 1